Assessment of nutrient intake and levels of nutrition knowledge, attitude, and practice among gymnasium users in Jordan - Moh’d, Al-Quran Mohammad Abdel-Hakim (2023)
Proper nutrition is important for physical performance of an individuals. However, lack of knowledge might lead to negative attitude and poor dietary practice. The purpose of this study is to assess nutrient intake and the levels of nutrition knowledge, attitude, and practice (KAP) among gymnasium users in Jordan. In this study, a total of 138 male gymnasium users (18 – 35 years) were recruited from several gymnasiums in Jordan. Their height and weight were measured, and body mass index (BMI) was calculated. The KAP-Sports nutrition questionnaires which contains 3 sections was administered. In addition, participants were asked to record their dietary intake in a given food diary for three days (two weekdays and one day on the weekend). Data were analysed using Nutritionist Pro Software and SPSS vs. 25.0 (Descriptive and Pearson correlation analysis). As a result, majority of the participants had moderate knowledge on sports nutrition (77.6%), neutral attitude (84.7%) and fair dietary practice (67.4%). The mean score for knowledge, attitude and practice was 18.07±2.56, 58.75±6.24 and 29.72±3.55 respectively. The correlation analysis revealed that there was a positive significant correlation between knowledge and attitude (p=0.048, r=0.18) as well as practice (p=0.018, r=0.20). The mean of daily total energy intake was 2085.7 ± 468.1 Kcals while the percentage out of total energy for CHO, protein and fat was 42%, 19%, and 39% respectively. The total energy and CHO intake were lower than the recommended value. Protein intake was within the RDA while fat intake was higher. The mean of daily Vitamin B6, Vitamin C, Vitamin E, calcium, magnesium, and zinc intake was 0.7 ± 0.3 mg, 98.0 ± 34.7 mg, 9.0 ± 1.8 mg, 823.5 ± 277.8 mg, 279.3 ± 64.3 mg, and 8.6 ± 1.1 mg respectively. Compared to the DRI value, participants’ micronutrients intake was lower except for Vitamin C and calcium. In conclusion, gymnasium users in Jordan did not have adequate knowledge that can affect positive attitude as well as good dietary practice. Sports nutrition education is recommended to ensure adequate and correct knowledge are disseminated to the athletes.